2020
DOI: 10.1080/20009666.2020.1751515
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the means of communication between nurses and resident physicians in the modern world: A community-based university hospital survey results

Abstract: Bachuwa (2020) Understanding the means of communication between nurses and resident physicians in the modern world: A community-based university hospital survey results,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…9 Skilled communication is crucial in providing excellent patient care and job satisfaction. 9,26 Poor communication is a leading cause of burnout, 27,28 , and practitioners who get training in communication are less likely to have burnout. 16,29,30 Despite that skilled communication was interpreted as good, the item "zero tolerance for disrespect and abuse" showed the lowest score (3.17) among all items in the HWEAT, which presents a need for further attention.…”
Section: Discussionmentioning
confidence: 99%
“…9 Skilled communication is crucial in providing excellent patient care and job satisfaction. 9,26 Poor communication is a leading cause of burnout, 27,28 , and practitioners who get training in communication are less likely to have burnout. 16,29,30 Despite that skilled communication was interpreted as good, the item "zero tolerance for disrespect and abuse" showed the lowest score (3.17) among all items in the HWEAT, which presents a need for further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication between nurses and physicians may contribute to an organisation's ability to improve patient outcome reliability (Stucky, Wymer et al, 2022 ). Despite the hope of technology integration as a means of improving communication, there is still work to be done regarding information exchange and its impact on patient care delivery (Haykal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When used properly, this toolkit can ensure that new nurses are equipped to handle sharing information in a timely manner, notify providers of critical changes in the patient9s status, and communicating changes or hold ups in patient care (Hettinger et al, 2020;Song & McCreary, 2020). Haykal et al (2020) highlighted that the relationship between nurses and health care providers must be complimentary, but that in order for this too occur, education and the implementation of communication strategies are essential (Haykal et al, 2020).…”
Section: Literature Discussion Summarymentioning
confidence: 99%
“…Majority of the reviewed articles strongly encouraged the implementation of strategies to improve communication between nurses and health care providers. NRPs should be designed to allow for interactive sessions on effective communication skills among team members (Bae et al, 2020;Haykal et al, 2020;Wang et al, 2018). Song & McCreary (2020) concluded that new graduate nurses need to be provided with opportunities for further development of competencies such as teamwork, critical thinking, and communication skills.…”
Section: Discussionmentioning
confidence: 99%